2011
DOI: 10.1097/bsd.0b013e3182024c06
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Mass Screw Complications

Abstract: Our clinical findings indicate that lateral mass fixation can be used safely with minimal complications and low rate of morbidity for cervical myelopathy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 0 publications
3
66
0
1
Order By: Relevance
“…The incidence rate of a screw implanted into the intervertebral foramen was 0.876% (mostly in C6), and the incidence rate of joint process injury was 1.433% (mostly in C3). In another study, analysis based on 325 cases and 1,662 lateral mass screws showed that there were 27 screws causing lateral vertebrate mass fractures, only three double cortical screws causing nerve damage, and three cases with loose screws that were pulled out 34. Overall, the incidence rate of complications related to internal fixation was low.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence rate of a screw implanted into the intervertebral foramen was 0.876% (mostly in C6), and the incidence rate of joint process injury was 1.433% (mostly in C3). In another study, analysis based on 325 cases and 1,662 lateral mass screws showed that there were 27 screws causing lateral vertebrate mass fractures, only three double cortical screws causing nerve damage, and three cases with loose screws that were pulled out 34. Overall, the incidence rate of complications related to internal fixation was low.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, a total of 10 studies were ultimately included in the analysis of LMS. 9,[15][16][17]25,36,42,[47][48][49] One study was prospective and 9 studies were retrospective. These studies included 766 patients in total, in whom 5328 screws were inserted from C-3 to C-7 ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Heller et al [30] found that the vertebral arteries of 26 cadaver specimens were not threatened, after undergoing LSF surgery of the lower cervical spine with the techniques of Roy-Camille and Magerl. Based on the findings of Heller, Katonis et al [4] found no cases of vertebral artery injury among the 225 patients who underwent LSF surgery. Lastly, although comparisons had been previously conducted, the pullout force of the implanted screws, with the application of different LSF techniques, is still controversial [31].…”
Section: Discussionmentioning
confidence: 99%
“…Even though numerous anatomical and clinical studies pointed out that the techniques of Roy-Camille and Magerl had the best practical applications, inevitable and undesirable complications still occurred, such as adjacent facet joint injury, nerve root, and vertebral artery or screw loosening and fracture [3]. In fact, all LSF techniques may result to diverse complications, depending on the surgeon’s optimization of the LSF techniques [4,5]. For the last two decades, many studies have evaluated the advantages of different LSF techniques, based on its complications [6-8].…”
Section: Introductionmentioning
confidence: 99%